Intra-Articular Osteoid Osteoma Mimicking Juvenile Arthritis. (17th July 2014) - Traore, Sidi Yaya; Dumitriu, Dana Ioana; Docquier, Pierre-Louis
Abstract : In case of intra-articular osteoid osteoma, misdiagnosis as juvenile arthritis may occur, delaying adequate treatment. We report cases of intra-articular osteoid osteomas in children that were misdiagnosed and initially inappropriately treated with intra-articular corticoid injection. Diagnosis of osteoid osteoma was finally given by CT-scan and appropriate treatment by radiofrequency ablation or surgical ablation was performed. Clinicians and radiologists should be aware of the potentially confusing clinical and imaging findings associated with intra-articular osteoid osteoma.